MANAJEMEN INFORMASI RUMAH KOST “Restra” - Ni Luh Gede Ambaradewi; I Wayan Dika (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2021)
The needs of the lodging house have been increased significantly due to the increasing number of newcomers and society's awareness of the importance of continuing education to the higher stages, especially in Denpasar. Realizing the high demand for the lodging house, Restra Kost develops website-based system information which helps the lodgers and the administrators to exchange the information effectively and efficiently. The development of this system is accomplished by Waterfall method, using flowchart, Use Case, ERD Database konseptual, Interface Design for modeling, , PHP for programming language and MySQL for databases. This research resulted in an application for lodging kost management in Agus Kost web-based. The existence of this system can facilitate guest, member and admin in the process of communication and management of lodging house.